Effect of the presence of pre-service construction cracks in concrete decks on the thermal profile of composite steel-concrete bridges in cold regions - Abi Shdid, Caesar (2017)
Thermally induced stresses in composite steel-concrete bridges are higher than those experienced by their concrete and steel cousins, leading to significant damage in the concrete deck and corrosion of the steel reinforcement. Bridge design engineers use thermal profiles prescribed by codes such as AASHTO to predict future service stresses. A 3D finite element model is presented that investigates the temperature distribution in a case study bridge with pre-existing construction deck cracks. The non-linear transient simulation is performed using actual environmental loads for a geographic region with severe climate (North Dakota), and the resulting profile is compared to that of AASHTO. The results show the thermal gradient proposed by AASHTO to be overly conservative in cold regions. Existing models seem to ignore the nonlinearity of the thermal gradient, which can be critical for thermal stress calculations. The pre-service deck cracks appear to have a considerable effect on both the vertical and the longitudinal temperature distributions, and it is recommended that they be given careful consideration by design codes.